Leadership Education and Development for What?: Civic Imagination for a More Just and Democratic Society - Brandon W. Kliewer; Jeff Zacharakis (Educational Considerations, 2015)
When institutions assign meaning to individual rights and distribute resources in ways that shape the life chances of people, if appropriately designed they strengthen social justice aims. Yet the natural outcome of how individuals relate to institutions does not automatically align with justice.
Keywords: editor introduction